Impact of globalization on the environment in major CO2-emitting countries: Evidence using bootstrap ARDL with a Fourier function - Wu, Cheng-Feng; Chang, Tsangyao; Wu, Tsung-Pao; Leng, Kai-jun; Lin, Meng-Chen; Huang, Shian-Chang (Frontiers in Public Health, 2022)
Alongside sustainable development as a major global aim, the contribution made by globalization to environmental issues has become crucial in recent decades. Prior studies have focused on how trade in globalization influences the environment. However, multiple economic, social, and political factors are also important, the integration of which needs to be considered in sustainable development. Sharp and smooth breaks in time series models are the consequence of real-world structures. Using the bootstrap autoregressive-distributed lag test with a Fourier function, the present study reexamined the nexus between globalization and the environment in China, the United States, and India. The empirical results indicate that in the United States, the nexus between globalization and the environment is cointegrated in the long-term. In the short term, globalization is improving the environment in the United States and India. However, in China, globalization is resulting in environmental degradation. This research will assist policymakers in developing comprehensive strategies for sustainable development.